PENGARUH KOMITMEN DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU DI SMP NEGERI 3 KOTA PROBOLINGGO - jurnalmap map; Rifkiyati Hafifah (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
The aims of this study are to know the teacher's commitment, interpersonal communication, and teacher performance at SMP Negeri 3 Probolinggo; second, to know a significant influence on the commitment of teachers to teacher performance in SMP Negeri 3 Probolinggo city. Third, to know a significant influence on interpersonal communication on teacher performance in SMP Negeri 3 Probolinggo. Fourth, to know simultaneous influence of commitment and interpersonal communication on the performance of teachers in SMP Negeri 3 Probolinggo. The population in this study are all teachers who teach at SMPN 3 Probolinggo. While the sample taken is the entire teacher population except researchers, amounting to 40 people. The data in this study were analyzed by multiple regression using the SPSS program. The results showed that simultaneous commitment and interpersonal communication had a significant influence on the performance of teachers of SMPN 3 Probolinggo. Partially Interpersonal commitment and communication also have a significant influence on the performance of teachers of SMPN 3 Kota Probolinggo. And between the two variables that are more dominant in influencing the performance of Probolinggo SMPN 3 teachers is the Interpersonal communication variable. Key words: commitment, interpersonal communication, teacher performance